Simulations of the star-forming molecular gas in an interacting M51-like galaxy - Treß, Robin G.; Sormani, Mattia C.; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We present here the first of a series of papers aimed at better understanding the evolution and properties of giant molecular clouds (GMCs) in a gala
Gesehen am 17.02.2020